Feeding, body condition and reproductive investment of Astyanax intermedius (Characiformes, Characidae) in relation to rainfall and temperature in a Brazilian Atlantic Forest stream - Souza, Ursulla Pereira [UNESP]; Ferreira, Fabio C. [UNESP]; Braga, Francisco Manoel de Souza [UNESP]; Winemiller, Kirk O. (Wiley-Blackwell, 2015)
Life history theory seeks to explain how environmental variation selects for patterns of investment in growth and survival relative to production and survival of offspring. Seasonal variations in rainfall and temperature provide environmental cues for spawning by many tropical freshwater fishes. To investigate environment-life history associations, we conducted a one-year study of Astyanax intermedius in an Atlantic Forest stream of southeastern Brazil. Our analysis focused on temporal variation in feeding, body condition and reproduction in relation to rainfall and water temperature. For mature females, food intake was not significantly correlated with rainfall or temperature; however, body condition was negatively correlated with rainfall and water temperature. Female reproductive effort was positively correlated with water temperature, but did not vary with rainfall. For males and juveniles, there was no significant relationship between food intake or body condition and either environmental variable. Testis weight was negatively correlated with rainfall, but was not significantly correlated with water temperature. We detected a negative correlation between gonad mass with body condition and food intake for females but not for males. Our results differed from other studies in tropical and subtropical areas where rainfall has been shown to be positively correlated with fish reproductive effort. Our results indicate that reproductive effort of males is relatively constant throughout the year, whereas for females, it increases with increasing water temperature. This increase in reproductive investment in concert with an increasing temperature and metabolic rate may incur a trade-off with somatic growth and survival for this small stream fish.
Keywords: fecundity; life history; oocyte size; physiological trade-offs; neotropical fishes